Impact of Opioid Receptor, Mu 1 (OPRM1) Polymorphisms on Pain Sensitivity and Clinical Response to Opioid Analgesic Therapy - Zahari, Zalina; Ismail, Rusli (Current Pharmacogenomics and Personalized Medicine, 2013)
Polymorphisms in genes involved in pain processing contribute to variation in pain sensitivity and clinical response to opioid therapy. This paper reviews the evidence on how opioid receptor, mu 1 (OPRM1) polymorphisms might influence pain sensitivity, opioid dose requirements and opioid-related effects such as analgesia and side effects. For example, it is shown that (1) individuals with AG and GG genotypes (118G variant allele carriers) exhibit lower sensitivity to pressure pain (higher pressure pain thresholds) compared with wild-type subjects (AA genotype or 118A allele carriers), and (2)individuals with GG genotypes require higher opioid doses compared with those who are AA or AG genotypes. The pain scores increase with increasing number of 118G alleles. Patients with the AA genotype have a greater analgesic effect than those with 118G allele (AG or GG genotypes). Additionally, the presence of 118G allele is associated with a reduced risk of nausea in spite of a higher morphine use, lower vomiting episodes and lower severity score for pruritus. Notably, even though many studies investigated a possible role of the OPRM1 polymorphisms in the risk for altered pain sensitivity, opioid dose and analgesia and opioid-related side effects in patients with pain, the results are conflicting. More studies to characterize the effects of other candidate genes and the combined effects of multiple genes, demography and clinical variables in predicting the clinical response and opioid-related side effects are required and these should involve larger numbers of patients in different population types.
Keywords: opioid analgesics